Voltage and frequency dependence of negative capacitance behavior in a Graphene-TiO2 nanocomposite photoanode based on quantum dot sensitized solar cells - Yalcin, Mesut; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2019)
In this letter, we investigated negative capacitance (NC) effect in nanocomposite based quantum dot sensitized solar cells. TiO2 and graphene-TiO2 nanocomposite photoanode based on quantum dot sensitized solar cells (QDSSCs) were fabricated and the capacitance-voltage (C-V), capacitance-frequency (C-f) and conductance-voltage (G/omega-V) characteristics were studied by attention the series resistance (R-s) effect. Admittance spectroscopy of QDSSCs were measured in a variable voltage and frequency ranges of ( - 2 V) - ( + 2 V) and 10 kHz-10 MHz, respectively. Capacitance values are exhibited a behavior transition from the positive to negative value after 50 kHz. As the capacitance values decreases, conductance increases in the NC region. Negative capacitance effect of meaning that QDSSC indicates an inductive behavior. Inductive behavior, which means that electrons injects from fluorine-doped tin oxide (FTO) conductive glass electrode to photoanode (graphene-TiO2). Also, NC phenomenon has not form significant effect on R-s.
Keywords: Negative capacitance (NC); Quantum dot sensitized solar cells (QDSSCs); Graphene-TiO2; Admittance spectroscopy; Inductive behavior